1994
DOI: 10.1557/proc-356-397
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Sputter-Deposited Nb5Si3 Film and Nb5Si3/Nb Microlaminates

Abstract: Monolithic Nb5Si3 films and microlaminates consisting of alternating, equally thick layers of Nb and Nb5Si3 were synthesized by magnetron sputtering. Thick monolithic Nb5Si3 films (25,000 nm) were deposited on a sapphire substrate to set process parameters and evaluate the microstructure and mechanical properties of as-deposited crystalline films. Nb5Si3/Nb micro-laminates with modulation wavelengths (i.e., bilayer thickness) of 40 and 200 nm were deposited on Nb substrates. Mechanical properties (elastic modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This suggests that most of the NbsSia layer is still amorphous or at least fine grained, even at these high deposition temperatures. Rawal et al [7] have shown that depositing at 750°C resulted in crystalline NbsSis. However, this temperature range could not be obtained in our current deposition chamber.…”
Section: Vapor Deposition At Elevated Temperaturesmentioning
confidence: 99%
“…This suggests that most of the NbsSia layer is still amorphous or at least fine grained, even at these high deposition temperatures. Rawal et al [7] have shown that depositing at 750°C resulted in crystalline NbsSis. However, this temperature range could not be obtained in our current deposition chamber.…”
Section: Vapor Deposition At Elevated Temperaturesmentioning
confidence: 99%